2017
DOI: 10.1152/ajpgi.00027.2017
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol metabolism by alcohol dehydrogenase or cytochrome P4502E1 differentially impairs hepatic protein trafficking and growth hormone signaling

Abstract: The liver metabolizes alcohol using alcohol dehydrogenase (ADH) and cytochrome P 2E1 (CYP2E1). Both enzymes metabolize ethanol into acetaldehyde, but CYP2E1 activity also results in the production of reactive oxygen species (ROS) that promote oxidative stress. We have previously shown that microtubules are hyperacetylated in ethanol-treated polarized, hepatic WIF-B cells and livers from ethanol-fed rats. We have also shown that enhanced protein acetylation correlates with impaired clathrin-mediated endocytosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 41 publications
2
23
1
Order By: Relevance
“…The liver metabolizes alcohol by ADH and cytochrome P450 2E1 (CYP2E1), while both the process of metabolism and the resulting metabolites induce the production of ROS, which intensify oxidative stress [34]. However, in the present study, no differences in the level of TBARS were found in the liver of the studied groups compared with the control animals.…”
Section: Discussioncontrasting
confidence: 65%
“…The liver metabolizes alcohol by ADH and cytochrome P450 2E1 (CYP2E1), while both the process of metabolism and the resulting metabolites induce the production of ROS, which intensify oxidative stress [34]. However, in the present study, no differences in the level of TBARS were found in the liver of the studied groups compared with the control animals.…”
Section: Discussioncontrasting
confidence: 65%
“…The variance analysis results showed that FRAP activity was influenced by the ethanol concentration (X1), the linear effect of extraction temperature (X3), the second-order interaction of ethanol concentration (X1 2 ), the reciprocal action of ethanol concentration and sample to solvent ratio (X12), the ethanol concentration and extraction temperature (X13), and the extraction temperature and extraction time (X34) ( Table 2). Among these, X1, X1 2 , and X13 showed largest F-value regression, and thus stronger dependency. The removal of the factors that did not influence the model led to the formation of the second-order polynomial equation given below:…”
Section: Effect Of Extraction Variables On Frapmentioning
confidence: 97%
“…Alcohol in the human body is first converted to acetaldehyde via the oxidation process, mediated by alcohol dehydrogenase (ADH) in the liver, and then converted to acetic acid via the same process, but mediated by aldehyde dehydrogenase (ALDH) [1]. The oxidation pathway used to metabolize alcohol in the liver is largely governed by three enzymes: ADH, cytochrome P450 2E1 (CYP2E1), and catalase (CAT) [2]. The reactive oxygen species (ROS) generated from excessive alcohol consumption are known to oxidize intracellular macromolecules, such as DNA, proteins, and lipids, and induce oxidative stress in the liver, causing functional damages.…”
Section: Introductionmentioning
confidence: 99%
“…Our data demonstrated that cardiac TFEB gene expression was significantly downregulated in ethanol‐fed rats compared with both control groups; this impairment in transcriptional regulation of lysosomal functioning could be indebted to the ability of ethanol metabolites to disturb protein trafficking through faulty microtubule assembly, disrupting both microtubule content and function . Furthermore, hesperidin administration resulted in significant upregulation of cardiac TFEB gene expression, thus implicating stimulation of autophagy‐lysosome machinery.…”
Section: Discussionmentioning
confidence: 71%